Assessing the impact of eccentricity, slabs, and transverse beams on the behavior of reinforced concrete beam-column joints. (March 2023) - Choi, Myeong-Ho; Lee, Chang-Hwan
Abstract: In this study, a cyclic lateral load experiment was performed to assess the behavior of reinforced concrete (RC) beam-column joints with non-seismic detailing. For the experiment, eight full-scale joint specimens were prepared; the experimental variables were eccentricity, presence of slabs, and number of transverse beams. Most experimental objects showed joint shear failure after beam yielding, and their eccentricity reduced the joint shear strength. Although the joints had non-seismic details, the presence of the slabs and increased number of transverse beams strengthened the confinement within the joints, thereby enhancing the joint shear strength. The joint shear strength that was calculated based on the equation suggested in ASCE 41-17 showed a substantial discrepancy from the actual measurement, primarily because the calculation neglected the impact of the slabs and number of transverse beams. Therefore, to improve the performance prediction, an actual three-dimensional shape of the joints must be considered. Additionally, based on further research outcomes, more factors that affect joint behavior must be considered in future relevant standards.